Recent physiological, genetic, and management perspectives on lodging resistance in rice - Ranjan Kumar Jena; Baneeta Mishra; Soumya Mohanty; Nalini Kanta Choudhury; Swagatika Das; Darshan Panda; Nitish Kumar Jena; Abinash Mishra; Amrita Sharma; B. N. Devanna; Rameswar Prasad Sah; Awadesh Kumar; et al. (Planta, 2026)

Insights Into the Genetic Diversity and Population Structure of Fusarium spp. Associated With Rice Bakanae Disease in Eastern and North‐Eastern India Using Microsatellite Markers - Raghu Shivappa; Prasanna S. Koti; Mathew S. Baite; B. Jeevan; C. Anilkumar; S. R. Prabhukarthikeyan; U. Keerthana; K. N. Shantha; Manas Kumar Bag; Shyamaranjan Das Mohapatra (New Zealand Journal of Botany, 2026)
Bakanae disease of rice has emerged as a major threat in the rice‐growingregions of Eastern and Northeastern India. Under field conditions, Fusarium species associated with bakanae disease of rice exhibit a significant degree of variability. Characterizing the pathogen and its isolates is crucial for understanding this variability. This study aimed to assess the genetic diversity and virulence patterns among 88 Fusarium isolates, the causal agents of rice bakanae disease, collected from various locations across Eastern and Northeastern regions of India. The isolates showed a significant variation in their morphology and virulence pattern. The genetic variability among isolates was assessed using 19 microsatellite markers, all of which were successfully amplified across the isolates. The observed genetic diversity was significant, as indicated by Shannon's information index for marker alleles. Using the marker allele differences among the isolates, pathogen population was subdivided into two groups. The analysis of molecular variance among two subpopulations demonstrated lower variance among population than within population. These findings suggest that the studied pathogen population comprises genetically distinct strains, ranging from highly virulent to moderately virulent. This study enhances our understanding of the diversity and distribution of Fusarium isolates, providing valuable insights for strategic breeding programs and effective disease management strategies.

Understanding the genetics of root system architecture in pigeonpea [Cajanus cajan (L.) Millsp.] - Krishna B. Gaiwal; Shruthi H. Belliappa; Naresh Bomma; Satheesh Naik; N . Sandhyakishore; Sagar K. Rangari; Ashwini Kalyan; Shivaji P. Mehtre; Anilkumar Vemula; Rahul Bhosale; Manish K. Pandey; Harish Gandhi; et al. (Theoretical and Applied Genetics, 2026)
Key message Field-based phenotyping of root system architectural (RSA) traits in a diversity panel (PI-GAP) of pigeonpea was conducted across three diverse pigeonpea growing environments along with identification of genomic regions associated with these traits through GWAS analysis. Abstract Root system architecture (RSA) plays a crucial role in plant stress tolerance mechanisms serving as the main route for water and nutrient acquisition, while also mediating plant-rhizosphere signalling. In the current study, an attempt was made to understand the genetic variability and genomic regions associated with RSA traits, as a relatively unexplored area of research in pigeonpea. The field-based “Shovelomics” approach was utilized to phenotype eight RSA traits: tap root length (TRL), lateral root length (LRL), number of lateral roots (NRL), stem diameter (SD), root diameter (RD), root angle from first and second lateral roots (RA1 and RA2) and root fresh weight (RFW) at physiological maturity. The pigeonpea international genome-wide association panel (PI-GAP) comprising of 185 genotypes from the reference set and 15 elite genotypes were used in the study. The combined ANOVA revealed significant genetic variance for all RSA traits except for RA2. Genome-wide association study was conducted using the Axiom Cajanus 56 K SNP array , leading to identification of 45 marker trait associations (MTAs) associated with RSA traits in pigeonpea. Multi-locus GWAS models detected six MTAs accounting for 4.84% to 18.73% of the phenotypic variation estimated (PVE) for TRL, 12 MTAs for LRL (4.73–13.92% PVE) and 11 MTAs for NLR (3.03–14.03% PVE value), respectively. Candidate gene analysis revealed genes associated with these traits, including BAG (Bcl-2-Associated athanogene) family molecular chaperone regulator 6 ( CcLG01_17476096 and CcLG01_17476721 ), root cap ( CcLG04_5972718 ) and Protein MAINTENANCE OF MERISTEMS (MAIN) ( CcLG06_8242342 ). These genes were found to have key roles in growth and establishment of roots under stress-related conditions in model crops. Further validation of identified MTAs would provide an opportunity to develop trait-specific markers paving the way for marker-assisted breeding in pigeonpea. Based on RSA traits, pigeonpea genotypes were categorized into deep, spreading and dimorphic root system. These classifications facilitate the phenotypic selection of genotypes for breeding against drought, heat, waterlogging and salinity adaptation. Improved cultivars with an ideal root architecture designed for efficient resource uptake and high yield under diverse environments could help address food security challenges in semi-arid tropics.

Dynamics of Total organic carbon: Partitioning, distribution and controlling processes in the Indian sector of the Southern Ocean during austral summer - Melena A. Soares; V. Venkataramana; R.K. Mishra; P. Sabu; R.K. Naik; Manish Tiwari; N. Anilkumar; R. Mohan; K. Mahalinganathan (Journal of Marine Systems, 2025)

Recurring eddies in the Southern Subtropical and Subantarctic Frontal regions of the Indian sector of the Southern Ocean during austral summer - P. Sabu; S. Cxynna; N.N.S. Vishnu; Nirmala J. Nair; Jenson V. George; N. Anilkumar; Rahul Mohan (Dynamics of Atmospheres and Oceans, 2025)

Microsatellite Marker–Driven Genetic Diversity and Breeding Potential Assessment in Okra (Abelmoschus esculentus (L.) Moench): A Multi-parent Approach - N. Sandeep; B. M. Dushyantha Kumar; Anilkumar Lalasing Chavan (Plant Molecular Biology Reporter, 2025)

Nutrient dynamics and biogeochemical processes at the Polar front of Indian sector of the Southern Ocean: Influence of Circumpolar deep water intrusion - Melena A. Soares; R.K. Mishra; P. Sabu; V. Venkataramana; R.K. Naik; A. Sarkar; R. Chacko; N. Anilkumar (Polar Science, 2025)

Ustilaginoidea virens, an emerging pathogen of rice: the dynamic interplay between the pathogen virulence strategies and host defense - Sunil Kumar Sunani; Prasanna S. Koti; N. C. Sunitha; Manoj Choudhary; B. Jeevan; C. Anilkumar; S. Raghu; Basana Gowda Gadratagi; Manas Kumar Bag; Licon Kumar Acharya; Dama Ram; Bishnu Maya Bashyal; et al. (Planta, 2024)

Phytoplankton community structure during the melting phase of the land-fast ice in Prydz Bay, east Antarctica - Pratiksha D. Deshmukh; Jenson V. George; Ravidas K. Naik; Shramik M. Patil; Melena A. Soares; Ajay Bhadran; N. Anilkumar (Polar Science, 2024)

Hydrography of the Southern Ocean fronts – The zooplankton link: A detailed study in the Indian Ocean sector - V. Venkataramana; R.K. Mishra; N. Anilkumar; Melena A. Soares; P. Sabu; A. Sarkar (Progress in Oceanography, 2024)

Revisiting population genetics with new genomic resources in dolichos bean (Lablab purpureus L. Sweet): an orphan crop - Vinayak Spoorthi; S. Ramesh; N. C. Sunitha; C. Anilkumar; M. S. Vedashree (Genetic Resources and Crop Evolution, 2024)

The Luna structure, India: A probable impact crater formed by an iron bolide - K.S. Sajinkumar; S. James; G.K. Indu; Saranya R. Chandran; Devika Padmakumar; J. Aswathi; S. Keerthy; M.N. Praveen; N. Sorcar; J.K. Tomson; Anil Chavan; Subhash Bhandari; et al. (Planetary and Space Science, 2024)

Focused identification of germplasm strategy (FIGS): a strategic approach for trait-enhanced pre-breeding - N. C. Sunitha; M. D. Prathibha; R. Thribhuvan; B. M. Lokeshkumar; P. S. Basavaraj; H. C. Lohithaswa; C. Anilkumar (Genetic Resources and Crop Evolution, 2024)

Plankton diversity and dynamics in the upper surface of the Indian sector of the Southern Ocean ecosystem and biogeochemical processes - Sreerag A.; Rajani Kanta Mishra; Ravidas K. Naik; V. Venkataramana; Melena A. Soares; Resha Mahale; N. Anilkumar; Mangesh Gauns (Regional Studies in Marine Science, 2023)

Cross frontal variability in bio-optical characteristics in the Indian sector of the Southern Ocean during an austral summer - Sudarsana Rao Pandi; Sarat C. Tripathy; S.S. Shaju; N. Anilkumar (Regional Studies in Marine Science, 2023)

Interannual variability of surface bio-optical characteristics in the frontal zones of the Indian sector of the Southern Ocean during austral summer - Sudarsana Rao Pandi; Sarat C. Tripathy; S.S. Shaju; P. Minu; Anvita U. Kerkar; C.C. Bajish; N. Anilkumar (Polar Science, 2023)

Advances in integrated genomic selection for rapid genetic gain in crop improvement: a review - C. Anilkumar; N. C. Sunitha; Harikrishna; Narayana Bhat Devate; S. Ramesh (Planta, 2022)

Unravelling genetic architecture and development of core set from elite rice lines using yield-related candidate gene markers - Rameswar Prasad Sah; Sasmita Behera; Sushant Kumar Dash; T. P. Muhammed Azharudheen; Jitendriya Meher; Awadhesh Kumar; Bishnu Charan Marndi; Meera Kumari Kar; H. N. Subudhi; C. Anilkumar (Physiology and Molecular Biology of Plants, 2022)

High-frequency noise and depth error associated with the XCTD/XBT profiles in the Indian Ocean sector of Southern Ocean and southwestern tropical Indian Ocean - Jenson V George; N Anilkumar (Journal of Earth System Science, 2022)

Assessment of natural DNA methylation variation and its association with economically important traits in dolichos bean (Lablab purpureus L. Var. Lignosus) using AMP-PCR assay - H. Ajaykumar; S. Ramesh; N. C. Sunitha; C. Anilkumar (Journal of Applied Genetics, 2021)

Recent Freshening, Warming, and Contraction of the Antarctic Bottom Water in the Indian Sector of the Southern Ocean - N Anilkumar; Babula Jena; Jenson V. George; Sabu P; Kshitija S; M Ravichandran (Frontiers in Marine Science, 2021)
High saline and cold Antarctic Bottom Water (AABW) forms around the continental margin of Antarctica that ventilates into the global ocean. To study the recent changes in AABW, we have analyzed the in situ observations collected from Indian Ocean expeditions to the Southern Ocean during 2010, 2011, 2017, 2018, and 2020. A comprehensive analysis of these observations indicated recent freshening, warming, and contraction in the layer thickness of the AABW. Even though the AABW depicted inter-annual variability, it changed to moderately fresher and lighter water mass at the end of the recent decade. The characteristics of AABW exhibited a contraction in its layer thickness (∼50–120 m) during recent years. The water mass showed its freshening (∼0.002) and warming (∼0.04°C) tendency from 2018 to 2020. The recent warming (∼0.3°C) of Circumpolar Deep Water (CDW) near the Prydz Bay suggests enhanced melting of ice shelves. It is hypothesized that the combined influences of onshore intrusion of warm CDW, upper ocean warming, sea ice decline, wind forcing, polynya, and calving events possibly caused the freshening and reduction in the thickness of AABW. The continued changes in the ocean-atmospheric environmental conditions and the subsequent changes in the bottom water characteristics likely influence the global climate, overturning circulation, and the biogeochemical cycle.

Potential Role of Major Phytoplankton Communities on pCO2 Modulation in the Indian Sector of Southern Ocean - Amit Sarkar; Rajanikant Mishra; Parli V. Bhaskar; N. Anilkumar; Prabhakaran Sabu; Melena Soares (Thalassas: An International Journal of Marine Sciences, 2021)

Distinctive Community Patterns With Exceptional Diversity of Polychaetes Around a Tectonically Active Archipelago in the Tropical Indian Ocean - Aiswarya Gopal; K. U. Abdul Jaleel; Usha V. Parameswaran; V. N. Sanjeevan; A. V. Saramma; Anilkumar Vijayan; N. Saravanane; G. V. M. Gupta; M. Sudhakar (Frontiers in Marine Science, 2020)

Temperature and phytoplankton size class biomass drives the zooplankton food web dynamics in the Indian Ocean sector of the Southern Ocean - V. Venkataramana; N. Anilkumar; R. K. Naik; R. K. Mishra; P. Sabu (Polar Biology, 2019)

Overfishing and Climate Drives Changes in Biology and Recruitment of the Indian Oil Sardine Sardinella longiceps in Southeastern Arabian Sea - Vasant Kripa; Kolliyil S. Mohamed; K. P. Said Koya; R. Jeyabaskaran; D. Prema; Shelton Padua; Somy Kuriakose; P. S. Anilkumar; Preetha G. Nair; T. V. Ambrose; A. M. Dhanya; K. S. Abhilash; et al. (Frontiers in Marine Science, 2018)

Moisture rainout fraction over the Indian Ocean during austral summer based on $$^{18}\hbox {O}/{}^{16}\hbox {O}$$ 18 O / 16 O ratios of surface seawater, rainwater at latitude range of 10°N–60°S - K Prasanna; Prosenjit Ghosh; S K Bhattacharya; P Rahul; Kei Yoshimura; N Anilkumar (Journal of Earth System Science, 2018)

Nitrogen uptake by phytoplankton in surface waters of the Indian sector of Southern Ocean during austral summer - S. C. Tripathy; Sivaji Patra; K. Vishnu Vardhan; A. Sarkar; R. K. Mishra; N. Anilkumar (Frontiers of Earth Science, 2018)

Variability of fronts, fresh water input and chlorophyll in the Indian Ocean sector of the Southern Ocean - N Anilkumar; JV George; R Chacko; N Nuncio; P Sabu (New Zealand Journal of Marine and Freshwater Research, 2015)
The aim of this study was to understand the variability in the fronts and water masses, and the effect of melt water on the concentration of chlorophyll (Chl a ) in the Indian Ocean sector of the Southern Ocean using hydrographic data collected during the austral summer (February 2010 and 2011). The Southern Subtropical Front (SSTF) and Northern Sub Antarctic Front (SAF1) were found to be further south at 57°30′E than at 47–48°E. This southward shift of the fronts was consistent with the southward meandering (c. 2°) of the Antarctic Circumpolar Current (ACC) core from the western section to the eastern section, which could have been caused by the bottom topography. The intrusion of water masses also differed between the western and eastern transects of the study region as a result of the meandering of the ACC core. Fresh water layer thickness relative to the winter water in 2011 was more compared to that during 2010. This could have been due to the larger amount of sea ice that was present in the winter of 2010, which subsequently melted, resulting in the advection of melt water from the south and west of the study region. In situ observations and satellite data detected a high Chl a concentration (c. 0.38 mg m −3 ) south of the Northern Polar Front (PF1) in 2011, which was caused by this melt water.

Biological response to physical processes in the Indian Ocean sector of the Southern Ocean: a case study in the coastal and oceanic waters - N. Anilkumar; Racheal Chacko; P. Sabu; Honey U. K. Pillai; Jenson V. George; C. T. Achuthankutty (Environmental Monitoring and Assessment, 2014)

Genetic dissection of drought tolerance in chickpea (Cicer arietinum L.) - Rajeev K. Varshney; Mahendar Thudi; Spurthi N. Nayak; Pooran M. Gaur; Junichi Kashiwagi; Lakshmanan Krishnamurthy; Deepa Jaganathan; Jahnavi Koppolu; Abhishek Bohra; Shailesh Tripathi; Abhishek Rathore; Aravind K. Jukanti; et al. (Theoretical and Applied Genetics, 2014)

Gametophytic selection for wilt resistance and its impact on the segregation of wilt resistance alleles in chickpea (Cicer arietinum L.) - R. L. Ravikumar; G. N. Chaitra; Anilkumar M. Choukimath; C. D. Soregaon (Euphytica, 2013)

Relative Microalgal Concentration in Prydz Bay, East Antarctica during Late Austral Summer, 2006 - Rahul Mohan; Sunil Kumar Shukla; N. Anilkumar; M. Sudhakar; Satya Prakash; R. Ramesh (Algae, 2009)

Influence of ridges on hydrographic parameters in the Southwest Indian Ocean - N. Anilkumar; S. M. Pednekar; M. Sudhakar (Marine Geophysical Research, 2007)